The Clinical Disputes Forum code to candour. (January 2014) - Thomas, Elizabeth; Leigh, Bertie
Medical authorities have historically either been silent or circumspect about the role of candour in clinical relationships. Hippocrates told doctors to abstain from doing harm, not entertaining the possibility that they might be negligent, while in 1847 the American Medical Association declared that doctors have: 'a sacred duty … to avoid all things which have a tendency to discourage the patient and depress his spirits'. Being candid about an injurious mistake in the course of treatment would no doubt discourage even the worldliest of 19th century patients. However, in recent years, the focus has shifted: doctors in 21st century have an obligation to disclose even the most depressing of mistakes. This modern 'duty of candour' is found in a mish-mash of moral principles, regulatory guidelines and contractual agreements but following the Francis Report it will be buttressed by statute.